Perancangan Dan Implementa Sisistem Infomrasi Penjualan Pada minimarket Palm Mart Berbasis Multi Tier - Sabilla Royan; Irwansyah Irwansyah; Suryayusra Suryayusra (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
The Mini Market Palm Mart, which can be a market for sellers, is addressed in Housing Ogan Permata Indah, Jalan Opi Raya, Jakarta, Palembang. Palm Mart has 6 employees, where they have their respective roles, namely a cashier, 2 shopkeepers and arranging items at the Palm mart and 2 warehouse guards and 1 administration. From year to year, Palm Mart mini-market stores have experienced an increase but it is very limiting for sellers to place their merchandise in Palm Mart Stores, thus impacting on the amount of data processed and the quality of service to consumers. The solution to the problems that exist in Palm Mart Stores is by creating a multi-tiered sales information system to help employees at the Palm Mart. At this writing the author uses descriptive research methods and uses the method of developing the waterfall system and uses Unified Modelling Language analysis.